Red flags to screen for malignancy and fracture in patients with low back pain - Downie, Aron; Williams, Christopher M.; Henschke, Nicholas; Hancock, Mark J.; Ostelo, Raymond W. J. G.; Vet, Henrica C. W. de; Macaskill, Petra; Irwig, Les; Tulder, Maurits W. van; Koes, Bart W.; Maher, Christopher G. (British journal of sports medicine, 2014)
STUDY QUESTION What are the best red flags to indicate the possibility of fracture or malignancy in patients presenting with low back pain in primary, secondary, or tertiary care? - SUMMARY ANSWER Older age, prolonged corticosteroid use, severe trauma, and presence of a contusion or abrasion increase the likelihood of spinal fracture (likelihood was higher with multiple red flags); a history of malignancy increases the likelihood of spinal malignancy.
Gesehen am 20.07.2020